2016
DOI: 10.7314/apjcp.2016.17.2.703
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Expression of Bax, Bcl-2, p53, Cathepsin B, Caspase-3 and Caspase-9 in the HepG2 Cell Line Following Induction by a Novel Monoclonal Ab Hep88 mAb: Cross-Talk for Paraptosis and Apoptosis

Abstract: Monoclonal antibodies with specific antigens have been widely used as targeted therapy for cancer. Hep88 mAb is a monoclonal antibody which shows specific binding with anti-cancer effects against the HepG2 cell line. However, its mechanisms of action are still not completely understood. We examined cell cycling and apoptosis by flow cytometry and mRNA expression of factors involved in apoptosis and paraptosis in Hep88 mAb-treated HepG2 cells by real-time PCR. The cell-cycle analysis demonstrated that growth-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Recently, researchers found that Hep88 monoclonal antibodies can inhibit HepG2 cell lines and achieve antitumor effects. For these findings, Hep88 played its role by promoting the expression of p53, caspase 3, caspase 9, and apoptotic Bax proteins . The results implied that caspase 3 was very important for apoptosis of HepG2 cells, which agreed with this experiment.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, researchers found that Hep88 monoclonal antibodies can inhibit HepG2 cell lines and achieve antitumor effects. For these findings, Hep88 played its role by promoting the expression of p53, caspase 3, caspase 9, and apoptotic Bax proteins . The results implied that caspase 3 was very important for apoptosis of HepG2 cells, which agreed with this experiment.…”
Section: Discussionsupporting
confidence: 87%
“…To further explore the mechanism of miR-499-5p in H/R-induced H9c2 cells, the levels of related apoptotic proteins were determined by western blot. Bcl-2, Bax and caspase-3 are key regulators of apoptosis, and apoptosis mediated by the dysregulation of such three genes underlies a plethora of diseases (Fong et al 2017 ; Mitupatum et al 2016 ). Bcl-2 and Bax are important genes in Bcl-2 gene family, and Bcl-2 inhibits apoptosis, while Bax promotes apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Caspase-3 expression can effectively prevent cell apoptosis [29]. Activated Caspase-9 can effectively incise and activate downstream Caspase-3 to induce cell apoptosis [30]. Apoptotic signals stimulated by death receptor and its ligand system are transduced to regulatory Caspase-8 which then activates the effector Caspases to induce cell apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%